OPTIMALISASI POTENSI SUMBER DAYA MANUSIA DAN USAHA MIKRO KECIL MENENGAH MELALUI PELATIHAN DAN PENDAMPINGAN DI DESA MEGANG SAKTI IV KABUPATEN MUSI RAWAS - Murahman, Mardi; Ayub, Ayub; Tiansah, Agus; Suramto, Suramto; Sudarmiyati, Sudarmiyati; Rizki, Dimas; Trianah, Yeni (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Community service is a form of contribution of academics (lecturers and students) in overcoming problems in the community and for community development with the aim of providing education and improving the skills of the people of Benai Megang Sakti IV Village through efforts to optimize the potential of Micro, Small, and Medium Enterprises (MSMEs) through a series of strategies that include surveys, data collection, training, and MSME development through packaging aspects, branding, and digital marketing. The focus of this empowerment program is located in Benai Megang Sakti IV Village, Megang Sakti District, Musi Rawas Regency. This service program aims to improve the quality of MSME businesses in the area through concrete steps. In addition, the development of MSMEs through attractive packaging efforts and strong branding will help differentiate products from competitors and build a positive image in the eyes of consumers. The method of implementing service is Participatory Rulal Apraical (PRA) with lectures, discussions, and demonstrations. This method involves the community which is the target partner in the implementation of service activities. The results of the service activities are an increase in the knowledge and skills of partners regarding the utilization of the potential and digitalization of MSMEs, introducing the concept of local economic empowerment and the importance of digitalization in the development of MSMEs, the use of e-commerce platforms to increase sales of local products, and also the achievement of product manufacturing that utilizes the local potential of the village, which in turn is expected to improve the local economy, create jobs and can optimize their potential and improve the quality of their business in a sustainable manner.